PERFORMANCE ASSESSMENT METRICS FOR IN SITU BIOREMEDIATION OF DNAPL SOURCE ZONES - Wealthall, Gary; Zeeb, Peter (Águas Subterrâneas, 2011)
Performance assessment of in situ remediation technologies may be limited by uncertainties in the spatial description of contaminant distribution and by the interpretative methods available to quantify mass depletion. A detailed case study of enhanced in-situ bioremediation (EISB) of a chlorinated solvent dense non-aqueous phase liquid (DNAPL) source zone provides a comparison of DNAPL mass depletion with dissolved phase mass flux reduction. The study concludes that EISB is effective at reducing DNAPL source mass and that reducing uncertainty in whether remedial targets have been reached requires increasing investment in performance monitoring.